The Non-hydrostatic Icosahedral Atmospheric Model: description and development - Satoh, Masaki; Tomita, Hirofumi; Yashiro, Hisashi; Miura, Hiroaki; Kodama, Chihiro; Seiki, Tatsuya; Noda, Akira T; Yamada, Yohei; Goto, Daisuke; Sawada, Masahiro; Miyoshi, Takemasa; Niwa, Yosuke; et al. (Progress in earth and planetary science, 2014)
This article reviews the development of a global non-hydrostatic model, focusing on the pioneering research of the Non-hydrostatic Icosahedral Atmospheric Model (NICAM). Very high resolution global atmospheric circulation simulations with horizontal mesh spacing of approximately O (km) were conducted using recently developed supercomputers. These types of simulations were conducted with a specifically designed atmospheric global model based on a quasi-uniform grid mesh structure and a non-hydrostatic equation system. This review describes the development of each dynamical and physical component of NICAM, the assimilation strategy and its related models, and provides a scientific overview of NICAM studies conducted to date.